The Hachioji specialty tengu's love. 1 - Nanao, Tomo (Yen Press, 2024)
"Can a determined tengu bride change a lonesome bachelor's ways? Well, it's not like he's got much of a choice-- 'cos she's already moving in! Young systems engineer Kotarou has had to make his own way in life. Nothing remains of his early childhood before he was orphaned--nothing except his grandparents' antique house in Hachioji and memories of Hime, the winged spirit girl he's come to dismiss as a youthful flight of fancy. But after his return to Hachioji and reunion with Hime, it becomes impossible to deny the existence of his fine, feathery friend--especially given that she's declared they're getting married at second sight!" -- Publisher's website.